Molecular diversity from aromatics. Cycloaddition of cyclohexa-2, 4-dienones, ring-closing metathesis and sigmatropic shifts: a general and stereoselective route to novel spirocarbocyclics. Issue 4 (28th January 2015) - Singh, Vishwakarma; Das, Beauty; Jarhad, Dnyandev B.; Mobin, Shaikh M.
Abstract: A novel, general and stereoselective route to spiroannulated bicyclo[2.2.2]octenones and their transformation to spiroannulated bicyclo[3.3.0]- and bicyclo[4.2.0]octanes is described. Oxidative dearomatization of o -hydroxymethylphenols, cycloaddition of spiroepoxycyclohexadienones, ring-closing metathesis and photochemical sigmatropic 1, 2- and 1, 3-acyl shifts are the key features of our methodology. Graphical abstract: